Análisis del comportamiento de queja del consumidor: Una investigación exploratoria en el contexto de los restaurantes - B. Moliner Velázquez; Gloria Berenguer Contrí; Irene Gil Saura; M. Fuentes Blasco (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2008)
The aim of this paper is to analyze the contribution that a set of the determinants has on the complaint behavior, with the purpose of identifying which combination of them can explain better the complaint responses, third parties responses and private responses. Our study has been made in the restaurants' context, and the methodology has been based on multiple regression models (Stepwise Method Regression). The most relevant results indicate that the probability of complaint's success is the variable that greater influence has on the compliant responses, whereas the level of dissatisfaction has the greater effect on private responses.
Keywords: 330; dissatisfaction; complaining behavior; complaint responses; private responses